Contributions to Architectural and Urban Resilience Through Vulnerability Assessment: The Case of Mozambique Island’s World Heritage - Susana Milão; Telma Ribeiro; Mariana Correia; Isabel Clara Neves; Joaquim Flores; Olga Alvarez (Heritage)
Mozambique Island, a UNESCO World Heritage property, faces significant challenges due to climate change and extreme weather events. This study proposes a comprehensive framework for assessing morphological vulnerabilities and enhancing urban resilience in this unique historical urban landscape. The research methodology involves a thorough analysis of historical cartography, urban evolution, topography, and vernacular architecture, combined with recent conservation assessments and case studies from other climate-vulnerable regions. This study reveals the island’s dual urban structure, comprising the Stone and Lime town and the Macuti town, each with distinct morphological characteristics and vulnerabilities. Historical maps and topographical analysis demonstrate how the island’s geography has shaped its urban development, with the Stone and Lime town built on higher ground and the Macuti town situated at or below sea level, increasing its flood risk. The research highlights the importance of integrating traditional knowledge with resilience strategies while respecting the authenticity and integrity of the World Heritage property. Key findings include the need for a GIS-based management tool for continuous conservation assessment, and the crucial role of community engagement in implementing resilience mechanisms. This study contributes to the broader discourse on cultural heritage as a contributor to architectural and urban resilience, offering valuable insights for other World Heritage properties facing similar climate challenges. The proposed framework emphasizes the importance of balancing heritage preservation with adaptive strategies, while enhancing the island’s resilience facing climate-related threats.